Design of Al-Islam and Muhammadiyah Curriculum Based on Deep Learning in Forming Muhammadiyah Identity of Students at Muhammadiyah University Purwokerto - Firdaus Firdaus; Hermawan Hermawan (Universitas Muhammadiyah Surakarta, 2025)
This study aims to design an innovative Al-Islam and Muhammadiyah (AIK) curriculum based on a deep learning pedagogical framework to strengthen the formation of Muhammadiyah identity among students at Muhammadiyah University Purwokerto. The research addresses the limitations of conventional AIK learning models that remain predominantly cognitive, normative, and ritualistic, and have not yet effectively facilitated value internalization and identity construction. The study employs a design-based research (DBR) approach by integrating Muhammadiyah theological foundations, educational psychology of identity formation, and deep learning pedagogy. The curriculum design is developed through iterative stages of analysis, design, development, implementation, and evaluation. Deep learning principles applied include meaningful learning, reflective engagement, critical consciousness, value internalization, and transformative praxis. Data were generated through document analysis, focus group discussions, expert validation, and limited pilot implementation within the AIK learning context. The study produces a structured AIK curriculum model consisting of learning outcomes, learning pathways, instructional strategies, learning activities, assessment frameworks, and identity-based learning indicators. The model is organized into four integrative dimensions: theological grounding, ideological internalization, socio-cultural engagement, and civic-ethical praxis. The curriculum systematically transforms AIK learning from doctrinal transmission into a process of identity formation, enabling students to embody Muhammadiyah values in personal, social, and civic life. This research offers an original contribution by integrating deep learning pedagogy with Islamic curriculum design and identity-based education within Muhammadiyah higher education. Practically, the model provides a scalable and adaptable framework for AIK curriculum reform across Muhammadiyah universities, supporting sustainable character formation, ideological internalization, and transformative student development in Islamic higher education institutions.